2014
DOI: 10.1109/tbme.2014.2323248
|View full text |Cite
|
Sign up to set email alerts
|

Automated Control of an Adaptive Bihormonal, Dual-Sensor Artificial Pancreas and Evaluation During Inpatient Studies

Abstract: Automated control of blood glucose in patients with type 1 diabetes has not yet been fully implemented. The aim of this study was to design and clinically evaluate a system that integrates a control algorithm with off-the-shelf subcutaneous sensors and pumps to automate the delivery of the hormones glucagon and insulin in response to continuous glucose sensor measurements. The automated component of the system runs an adaptive proportional derivative control algorithm which determines hormone delivery rates ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…The AP system architecture has been clinically evaluated for three potential configurations, based on the hardware platform where the controller was implemented, specifically: computer/laptop [7,[16][17][18], tablet [8,19,20] and smartphone [21]. In this study, we examine two possible AP hardware configurations; we refer to them as Configuration A and Configuration B.…”
Section: Hardware Configurations Of the Ap Systemmentioning
confidence: 99%
“…The AP system architecture has been clinically evaluated for three potential configurations, based on the hardware platform where the controller was implemented, specifically: computer/laptop [7,[16][17][18], tablet [8,19,20] and smartphone [21]. In this study, we examine two possible AP hardware configurations; we refer to them as Configuration A and Configuration B.…”
Section: Hardware Configurations Of the Ap Systemmentioning
confidence: 99%
“…In pre-approval studies the system has been shown to reduce hemoglobin A1C and glucose variability (34). Multiple other systems are being developed including a bihormonal system using insulin and glucagon (35).…”
Section: New Therapiesmentioning
confidence: 99%
“…The short answer to this question is therefore nodglucagon will not be essential for AP systems to reach the market. (29,43) Reduction in severe and moderate hypoglycemia (20,44) Reduction in time spent hyperglycemic and hypoglycemic and increased time in target range in outpatient settings (45) Reduction in time spent hyperglycemic and hypoglycemic and increased time in target range in outpatient settings (24,46) Reduction in hyperglycemia and hypoglycemia and increase in time in target in an inpatient settings (42,46) Reduction in hyperglycemia and hypoglycemia and increase time in target in outpatient setting (9) That said, results from insulin/glucagon studies have been outstanding and have generated enthusiasm in the field (9,30,31) and in the popular press (32). Conceptually, an insulin/glucagon approach is appealing.…”
Section: Key Question: Must Ap Systems Use Glucagon?mentioning
confidence: 99%